2022
DOI: 10.3390/life12010081
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Pathway Inhibition in Gastric Cancer: The Golden Era of an Old Target?

Abstract: Gastric cancer (GC) is the third leading cause of cancer-associated death worldwide. The majority of patients are diagnosed at an advanced/metastatic stage of disease due to a lack of specific symptoms and lack of screening programs, especially in Western countries. Thus, despite the improvement in GC therapeutic opportunities, the survival is disappointing, and the definition of the optimal treatment is still an unmet need. Novel diagnostic techniques were developed in clinical trials in order to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 88 publications
(99 reference statements)
0
22
0
Order By: Relevance
“… 434 When bound with fibroblast growth factors (FGF), FGFRs are activated through phosphorylation of the intracellular tyrosine kinase domain, which then activates several important cellular pathways, including the RAS/MAPK, the PIK3CA/AKT/mTOR, and the Janus kinase (JAK) pathways. 435 Activation of these signaling pathways can affect angiogenesis, cell mitosis, differentiation, proliferation, and invasive processes. 435 Dysregulation of the FGF-FGFR axis has been thought to contribute to GC carcinogenesis.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
See 1 more Smart Citation
“… 434 When bound with fibroblast growth factors (FGF), FGFRs are activated through phosphorylation of the intracellular tyrosine kinase domain, which then activates several important cellular pathways, including the RAS/MAPK, the PIK3CA/AKT/mTOR, and the Janus kinase (JAK) pathways. 435 Activation of these signaling pathways can affect angiogenesis, cell mitosis, differentiation, proliferation, and invasive processes. 435 Dysregulation of the FGF-FGFR axis has been thought to contribute to GC carcinogenesis.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“… 435 Activation of these signaling pathways can affect angiogenesis, cell mitosis, differentiation, proliferation, and invasive processes. 435 Dysregulation of the FGF-FGFR axis has been thought to contribute to GC carcinogenesis. Overproduction of FGF presumably promotes communication between epithelial and stromal cells in the tumor microenvironment, which is critical for tumorigenesis.…”
Section: Signaling Pathways In Gastric Cancer and Therapeutic Implica...mentioning
confidence: 99%
“…However, targeted drugs for GC treatment are very limited. Studies have revealed FGFR2 as a potential Frontiers in Pharmacology frontiersin.org target for GC treatment (Lengyel et al, 2022). Therefore, discovery targeted therapy for FGFR2 is very significant.…”
Section: Discussionmentioning
confidence: 99%
“…Use of FGFRs inhibitors might cause a series of problems such as mutations conferring resistance to FGFR-targeting drugs and side-effects ( Yue et al, 2021 ). On the other hand, due to the patient heterogeneity, FGFRs kinase inhibitors and anti-body drug conjugates had shown lower efficacy than expected, and drug toxicity, multiple GC treatment clinical trials targeted on FGFRs have not made any progress ( Repetto et al, 2021 ; Lengyel et al, 2022 ). Hence, the discovery of novel FGFRs inhibitors is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Gene alterations in the FGFR family (FGFR1, FGFR2, FGFR3, and FGFR4) have been reported in various cancers. Thus, pan-FGFR inhibitors have been developed and show antitumor effects against DGC in preclinical studies, and some of them have been tested in clinical trials [ 43 , 84 ]. As gene amplification of FGFR2 is the predominant FGFR alteration in DGC, the development of FGFR2-specific inhibitors may improve efficacy and reduce adverse effects.…”
Section: Targeting Rtks For Peritoneal Dissemination Of Dgcmentioning
confidence: 99%